Pengaruh Tekanan Injeksi terhadap Flow Length Material Polypropylene (PP) dengan Ketebalan Produk 1MM - Widjaja, Hartono; Fauzan, Mochammad (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2023)
Injection molding is the injection of melted plastic material into a mold to form a product. A good formulation of the injection process is affected by several factors, factors that affect the injection process include the plastic melt temperature, product design, injection speed and injection pressure. This study examines the parameters that affect the flow length of the polypropylene (PP) material. This material was chosen because it is commonly used in life, such as food and beverage containers. This study aims to determine how far the flowability of PP plastic with a product thickness of 1 mm is based on the table of reasonable design values for the L/t ratio in the book Molding Simulation: Theory and Practice. This research method goes through several steps including, creating a cavity layout to form the research specimens, analysis of specimen molds, trial molds with calculated parameters and changing injection pressure parameters gradually, measuring and assessing the resulting flow length of the injection trial process, concluding the experimental results. The results of this study are expected to be taken into consideration when designing a product made from PP so as to minimize failures in the mold making process.